Egypt : Inequality of Opportunity in Education - Ersado, Lire; Gignoux, Jérémie (Taylor and Francis, 2017)
The paper examines the levels and trends in access to education and educational outcomes across generations of Egyptian youth. Examination of four cohorts of individuals aged 25–29 shows that, although basic education has democratized, some inequities in access to general secondary and college education have persisted over the past 25 years. The analysis of test scores from TIMSS and national examinations in the late 2000s shows that more than a quarter of learning outcome inequality is attributable to circumstances beyond the control of a student, such as parental education, socioeconomic background, and birthplace. The high level of overall achievement inequality observed makes inequities in learning opportunities between Egyptian youth high compared to other countries in absolute levels. Moreover, learning gaps among pupils from different backgrounds appear at early grades. High and unequal levels of household expenditures in private tutoring and tracking into vocational and general secondary schools that depend on high stakes examination substantially contribute to unequal learning outcomes.